2020
DOI: 10.1111/ijn.12884
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and benefits of model development for integration of palliative care for cancer patients in a developing country: A qualitative study

Abstract: Aim The aim of the study was to identify barriers and benefits in establishing a model for integration of palliative care of cancer patients in daily clinical practice in tertiary health institutions. Methods This was a qualitative design study using in‐depth interviews with four stakeholders and focus group discussions with 19 nurse managers using purposive sampling to select the participants, utilizing interpretive paradigm method. Need was ascertained for a model that would guide nursing care for cancer pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The result aligns with previous studies that have reported that integration of PC enhances preparations towards the EoL. 20,34 For example, the result is consistent with the findings of Ndiok and Ncama 20 whose study revealed that integrating PC promoted meaningful EoL (i.e. preparing for the EoL).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The result aligns with previous studies that have reported that integration of PC enhances preparations towards the EoL. 20,34 For example, the result is consistent with the findings of Ndiok and Ncama 20 whose study revealed that integrating PC promoted meaningful EoL (i.e. preparing for the EoL).…”
Section: Discussionsupporting
confidence: 92%
“…The result corroborates the findings of earlier studies that have found interdisciplinary communication between primary healthcare providers and the PC team to have improved as a result of integrating care. 20,21…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding mirrors that of several studies. 2123 The present finding reveals that patients who ascribed their disease to spiritual causation often reported late for palliation. A plausible explanation for this could be that patients with poor knowledge and wrong perceptions about PC would want to assume a state of denial and explore all other options available to them before considering PC.…”
Section: Discussionmentioning
confidence: 54%